2003
DOI: 10.1142/s0218625x03005244
|View full text |Cite
|
Sign up to set email alerts
|

Electron-Stimulated Desorption of Positive Ions from Methanol Adsorbed on a Solid Ar Substrate

Abstract: Electron-stimulated desorption (ESD) of positive ions from weakly physisorbed molecules has been investigated. From methanol adsorbed on a solid Ar substrate, the protonated cluster ions of the type H+(CH3OH) n(n = 1 - 4) are emitted, together with the fragment ions such as [Formula: see text](n = 0 - 3), H3O+, CHO+, CH3O+, etc. The yields of these ions are markedly enhanced at the smallest coverage and decay steeply with increasing coverage. Coulomb explosion between valence holes confined in adsorbed nanoclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…The most intense desorbed fragment is the H + ion, what is consistent with the formation of a thick molecular film. 43 Also, light fragments, such as H + and H 2 + , have high initial kinetic energy, what lowers their residence time on surface, lessening their probability of neutralization. 44 In addition to H + and H 2 + , the H 3 + ion was also produced as a member of the H n=1-3 + ion series.…”
Section: Resultsmentioning
confidence: 99%
“…The most intense desorbed fragment is the H + ion, what is consistent with the formation of a thick molecular film. 43 Also, light fragments, such as H + and H 2 + , have high initial kinetic energy, what lowers their residence time on surface, lessening their probability of neutralization. 44 In addition to H + and H 2 + , the H 3 + ion was also produced as a member of the H n=1-3 + ion series.…”
Section: Resultsmentioning
confidence: 99%
“…The H 3 O + fragment is seen in both spectra of Figure . It is well-known , that water can be produced from alcohol dissociation on the ice phase. Some water cluster series like (H 2 O) n (H 3 O) + were identified in the desorption spectrum of ethanol at energies higher than 1400 eV, as shown in Table .…”
Section: Resultsmentioning
confidence: 99%
“…Such an effect reduces the Coulombic repulsion between the valence holes and lowers the probability of heavy fragments desorption. Kawanowa et al also mention that the proton transfer to the methanol molecule occurs during molecular collisions in the condensed phase. In fact, previous gas phase studies ,, showed no evidence of protonated molecular cluster formation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is noteworthy that the same comparison is valid for previous gas-phase experiments, with either photons or electron impact. ,, The reason for this is the influence of C–H···N intermolecular forces on the pyrimidine ice during fragmentation, which allows a number of rearrangements before desorption occurs. The role of intermolecular forces during ESID has been previously studied for condensed hydrogen-bonded molecules, suggesting that strong ion–dipole interactions may favor proton-transfer reactions, rather than simple molecular dissociation.…”
Section: Results and Discussionmentioning
confidence: 99%